2014
DOI: 10.1007/978-3-662-44188-6_27
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Listening and Speaking with Game-Based Learning Activities in Situational Context

Abstract: Abstract. This study proposed game-based learning activities in situational context to facilitate listening and speaking. To measure the feasibility of learning activities, this study conducted one experiment in which students participated at learning activities by using traditional method (control) and mobile application (experimental). Results revealed that experimental students outperformed control students in the speaking post-test while there was insignificant difference in the listening post-test. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…W.-Y. Hwang, Ma, Shadiev, Shih, and Chen (2015) suggested that if the learners use situational materials in their daily life, then they could recall what they had learned when they encountered the same scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…W.-Y. Hwang, Ma, Shadiev, Shih, and Chen (2015) suggested that if the learners use situational materials in their daily life, then they could recall what they had learned when they encountered the same scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…When performing drama using the AME, physical movement can create an interactive environment that leads students to develop their speaking fluency and vocabulary (Zhang et al, 2018;Zhou & Li, 2019). The authentic contexts (e.g., playgrounds, libraries, and corridors) can enhance students' interests and speaking skills (Hwang et al, 2015;Zhang et al, 2018). In addition, using drama in authentic contexts made learning experiences meaningful and fun (Gerva´s et al, 2016;Lombardo et al, 2017), as shown in interview results.…”
Section: Correlations Between Drama Learning Behaviors and Post-testsmentioning
confidence: 99%
“…With the advancement of technology, many researchers have explored the effect of mobile technology on student language learning (Chang & Hsu, 2011;Hwang et al, 2015;Zhang et al, 2018;Zhou & Li, 2019). However, only a few studies used mobile technology to improve and assist English drama learning activities for EFL learning (Zhang et al, 2018;Zhou & Li, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many different researches have been carried out to design applications and games for learning a language in different cultural contexts (Holden & Sykes, 2011 ; Hwang et al, 2015 ; Ishaq et al, 2021a ; Kuo & Lai, 2006 ; Lee et al, 2011 ) as regional factors influence the teaching and learning methods (Ishaq et al, 2021a ; Terry & Cheney, 2016 ). Various authors discussed considering localized content for language learning in their cultural context (Edge et al, 2011 ; Elaish et al, 2019a ; Marx & Pray, 2011 ; Tshering et al, 2018 ; Wierzbicka, 1985 ).…”
Section: Introductionmentioning
confidence: 99%